[OP.7A.10] THE BLOOD PRESSURE LOWERING EFFECT OF THE MOBIUSHD DEVICE IS INDEPENDENT OF PULSE PRESSURE. (September 2017) - Reuter, H.; Bates, M.C.; Devireddy, C.M.; Foster Iii, M.T.; Ghali, M.G.H.; Van Der Heyden, J.; Kroon, A.A.; Mendelsohn, F.O.; Eliasziw, M.; Spiering, W.
Abstract : Objective: The Framingham Heart Study showed an increased risk of cardiovascular disease with increasing pulse pressure (PP). Elevated PP is frequently observed with increasing age and may reflect the loss of elastic properties in large arteries. We investigated the effects of the MobiusHD-device on office systolic BP (SBP) and on 24-hour ambulatory BP (ABPM) in patients with high PP. Design and method: MobiusHD is designed to passively amplify pulsatile strain at the carotid sinus and reduce BP through increased baroreceptor activation, and consequently increase sympathoinhibition. A total of 40 patients were treated with MobiusHD for therapy-resistant hypertension and had BP measured at discharge, 1, 3, and 6 months. For analyses, patients were grouped according to baseline PP (high PP:>70 mmHg, n = 25; low PP:<70 mmHg, n = 15). Responsiveness at 6 months to MobiusHD treatment was defined as decrease in SBP of more than 10 mmHg, and also as decrease in ABPM of more than 5 mmHg. Linear mixed models were used to compare mean changes in BP over time between groups, chi-square tests were used to assess responsiveness. Results: Mean ± SD age was 53 ± 12 years and 50% were female. Baseline mean SBP, PP, and ABPM were 182 ± 17 mmHg, 74 ± 16 mmHg, and 165 ± 16 mmHg, respectively. Upon implantation of MobiusHD, SBP and PP were significantly reduced at 1, 3, 6 months by 21, 29, 25 mmHg (p<0.001) and by 13, 16, 12 mmHg (p < 0.001) in the high PP group and by 24, 16, 25 mmHg (p = 0.001) and by 11, 6, 11 mmHg (p = 0.009) in the low PP group, respectively. ABPM was significantly reduced at 3, 6 months by 15, 19 mmHg (p < 0.001) in the high PP group and by 14, 22 mmHg (p = 0.001) in the low PP group. There were no significant differences in overall reductions in SBP, PP, ABPM between the high and low groups (p = 0.64, p = 0.28, and p = 0.90 respectively). No significant differences in SBP responsiveness were observed between high and low baseline PP groups (68%vs.80%, p = 0.41), as well as ABPM responsiveness between high and low baseline PP groups (76%vs.73%, p = 0.85). Conclusions: The MobiusHD-device effectively reduced SBP, PP, and ABPM in patients with therapy-resistant hypertension. The SBP and ABPM responses to MobiusHD were not different between patients with high or low PP.